Relevansi Pertanggung Jawaban Menurut Undang-Undang Penanaman Modal Dan Undang-Undang Perseroan Terbatas Pada Sistem Investasi Indonesia - Haide Gelya Mulyana; Berlian Setiyowibowo; Yogi Eko Kurniawan (CV. SINAR HOWUHOWU, 2026)
This study examines the relevance of investor and director liability within Indonesia’s investment system based on Article 15 letter a of Law Number 25 of 2007 on Investment and Article 97 of Law Number 40 of 2007 on Limited Liability Companies. Problems arise when both regulations emphasize the principle of Good Corporate Governance (GCG), yet differ in their objects and subjects of regulation, potentially creating overlapping responsibilities in investment practices, particularly when losses or legal violations occur. This research employs a normative juridical method with statutory and conceptual approaches. The findings show that Article 15 letter a of the Investment Law serves as a normative obligation for investors to implement GCG, whereas Article 97 of the Company Law affirms the legal responsibility of directors in managing the company. These two provisions have a complementary relationship in establishing an accountable investment system; however, in practice, gaps in law enforcement still exist, especially concerning the implementation of fiduciary duties, the principle of prudence, and the application of the piercing the corporate veil doctrine in cases of negligence or abuse of authority. This study concludes that integrating both provisions is necessary to strengthen legal protection, increase certainty for investors, and clarify the boundaries of liability between investors and directors in creating a transparent and sustainable investment climate.